The business research paper : a manual of standards: including bibliographical sources for Reports-Thesis-Dissertations - Janis, J. Harold (Hobbs, Dorman , New York, 1967)
This manual aims to provide a compact guide to the form and mechanical style of business research papers. A supplementary aim is to introduce the researcher to the bibliographical source of business information
Includes bibliographical references p. 93-94.and index.
aia 08/05/2017
Loans
Keywords: Report writing; Business Research